Influencing Factors Nurse Behavior in Providing Service in Installation Distric General Hospital Praya Central Lombok - Teguh Achmalona; Sentot Imam Suprapto; Indasah Indasah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Nursing services are an integral part of health services in hospitals, which have a very strategic position in efforts to improve the quality of care in hospitals, thus demanding the professionalism of nurses in providing and regulating nursing care activities to patients. The purpose of this study was to determine the effect of leadership, competency, motivation, workload and reward factors on the behavior of nurses in providing services in installation distric general hospital Praya.The research design used was quantitative analytic with a cross sectional approach. The sampling technique uses cluster random sampling with a sample of 114 respondents. Data was collected using questionnaires and observation sheets, then analyzed using ordinal regression test. The results showed, from the results of a statistical test simultaneously obtained p value of 0.000 <α = 0.05, meaning that all independent variables together affect the dependent variable. The results of statistical tests partially obtained the results there is an influence between leadership, competence, motivation, workload and reward with nurse behavior, with p values ​​for each variable, namely leadership (p <0.012), competence (p <0.008), motivation (p <0.006), workload (p <0.012), and reward (p <0.000). Multivariate analysis shows that reward is the most dominant variable affecting the behavior of nurses in providing nursing services with a value (p <0,000). Nurse behavior is influenced by factors of leadership, competence, motivation, workload and rewards, so that these aspects need to be managed well in the hope of getting better results of nurse performance and behavior